The Social Construction of Identity in Criminal Cases: Cinema Verité and the Pedagogy of Vincent Chin - Johnson, Paula C. (1996)
This article will discuss the use of the film, Who Killed Vincent Chin?, as a method: (1) to analyze the relationship of social constructions of identity, particularly race, on the rules and discretionary application of criminal jurisprudence; (2) to provide an interactive pedagogical tool for law teachers, especially criminal law teachers, to examine the social contexts of criminal jurisprudence from multiple perspectives; and (3) to examine the ability of criminal law doctrine to address issues of race